Bridging the wage gap: A discussion of wage subsidies to low-paid workers and their costs in Italy - Luigi Bonatti; Lorenza Alexandra Lorenzetti; Silvio Traverso (Global Labor Organization (GLO), 2025)
This paper discusses the potential introduction of permanent public subsidies to supplement the wages of low-paid workers in Italy, taking inspiration from Edmund Phelps' ideas on supporting the working poor. We consider how a negative taxation scheme for low-wage earners might address structural labor market challenges such as low participation rates, labor market segmentation, and widespread in-work poverty. Using a stylized theoretical model, we illustrate how such subsidies could affect wages, employment, and labor supply-demand dynamics, with a particular focus on potential cost implications under different elasticity assumptions. We also consider how design features - such as targeting full-time workers or integrating the subsidy with broader social and economic reforms - could maximize the measure's impact while mitigating risks related to fraud or uneven coverage. Finally, a scenario analysis based on Italian Labor Force Survey data provides an indication of the policy's likely scale and distributional effects. The paper concludes by reflecting on both opportunities and challenges for implementing wage subsidies in Italy's segmented labor market.
Keywords: D04; H20; J20; J38; 330; Low-skilled workers; Working poor; Wage subsidies; Negative taxation